Matéria prima e ingredientes como fonte de contaminação de linguiças frescais por Salmonella spp - Thomazella, Francisco Marcos Dias [UNESP] (2005)
There were analyzed 19 portions of fresh sausage, each one of them corresponding to different lots and days of production. Salmonella spp was isolated in 9 of these portions (47,3%). On the 19 dough samples before the stuffing, the pathogen was isolated in 6 (31,6%) and on the final stuffed and ready for consumption product, in 3 (15,8%). The cuts of pork meat and bacon were the great responsible for the contamination observed, since on the 9 ones where it was detected, these were the raw material that were contaminated. On what concerns the beef meat, just in one sample it was found Salmonella, and on that production day the pork scraps were also contaminated. Any of the other ingredients has presented contaminated by the pathogen on the 19 portions of the product. When analyzed again through the multiple tubes technique (MNP), all the samples of the final product have shown values < 3,0 of Salmonella cells/g of the product. The contamination of fresh sausages on the present study has occurred basically for products of pork origin (meat scraps and bacon) used on the product elaboration. On the case of the plant in question, only a more rigorous control of the pork raw material acquired may reduce the contamination risk on the final product. Although this contamination occurs for a small number of cells, the fresh sausages endanger the consumer health